Using an online Learning Management System to personalise learning for primary students - Bronwyn Edmunds; Maggie Hartnett (Flexible Learning Association of New Zealand, 2014)
This paper reports on one aspect of a descriptive multiple-case study which set out to explore the role of a Learning Management System (LMS) in personalising learning for students from the perspective of three primary school teachers.  The intention was to provide insight into the role an LMS could play in classrooms when personalising learning.  The research project involved gathering multiple sources of data from interviews, observations and documentary information from the LMS. The findings suggest that an LMS has the potential to be a key part of a primary classroom environment which is built on the components of personalising learning.  For the teachers in this project, one salient component of personalising learning involved ensuring learning was built around assessment for learning pedagogy and the use of the LMS as a tool to support learning.  The findings highlighted the interconnected nature of personalising learning pedagogy, the LMS and classroom practice.